2003
DOI: 10.1002/gene.10205
|View full text |Cite
|
Sign up to set email alerts
|

Metaphase FISHing of transgenic mice recommended: FISH and SKY define BAC‐mediated balanced translocation

Abstract: The evolving trend to use larger transgenes and their associated increased chance of unexpected genetic events mandates more careful characterization of transgenic mice. In characterizing our five new mouse strains transgenic for the BAC, bEMS4, we have identified the highest copy number reported to date: the stable incorporation of approximately 40 copies of a 194-kb expressed transgene in a single insertion site. We caution, however, that standard molecular techniques failed to identify a balanced translocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Pronuclear injection of a 141 kb PAC clone spanning human NR2E1 (pacEMS1; clone identification number, dJ429G5; GenBank accession number AL078596.7) was performed as described previously (Abrahams et al, 2003) to produce eight transgenic founders from which five independent strains were established successfully. Two strains were used here [C57BL/6J.Cg-Tg(NR2E1pacEMS1B)10Ems and C57BL/ 6J.Cg-Tg(NR2E1pacEMS1D)11Ems] with mice at backcross generation 6 (N6) (98.4% C57BL/6J) to N10 (99.9% C57BL/6J) before use.…”
Section: Methodsmentioning
confidence: 99%
“…Pronuclear injection of a 141 kb PAC clone spanning human NR2E1 (pacEMS1; clone identification number, dJ429G5; GenBank accession number AL078596.7) was performed as described previously (Abrahams et al, 2003) to produce eight transgenic founders from which five independent strains were established successfully. Two strains were used here [C57BL/6J.Cg-Tg(NR2E1pacEMS1B)10Ems and C57BL/ 6J.Cg-Tg(NR2E1pacEMS1D)11Ems] with mice at backcross generation 6 (N6) (98.4% C57BL/6J) to N10 (99.9% C57BL/6J) before use.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, further detailed analysis around the translocation junctions revealed that the surrounding regions were composed of 13 fragments of defined transgenic chromosome origins over approximate-The integration of transgenes into a host genome requires chromosome breakages, which cause rearrangements such as deletions or translocations (Covarrubias et al, 1986;Gordon et al, 1989;Shawlot et al, 1989). Molecular cytogenetic analysis using SKY has characterised genetic events such as a balanced translocation and an integration site of transgenes in transgenic mice (Abrahams et al, 2003). Apparently simple rearrangements determined at the cytogenetic level may show up as more complex after sequence analysis of the breakpoints of chromosome rearrangements.…”
Section: Introductionmentioning
confidence: 99%
“…play a critical role in determining the statistical uncertainty between treatment groups. Although various laboratories have proprietary scoring criteria, scoring of 100 to 300 and 20 metaphase cell spreads with 40 well-separated chromosomes in at least 3 to 5 mice is generally recommended for determining statistical significance in mFISH and SKY analysis, respectively 24,25 . Moreover, the choice of nomenclature used to classify aberrations in painted chromosomes is an important parameter for assessing statistically uncertainty.…”
Section: Discussionmentioning
confidence: 99%